Fundamentals of enzyme kinetics - Cornish-Bowden, Athel (Wiley-Blackwell, 2012)
Now in its fourth edition, this textbook is one of the few titles worldwide to cover enzyme kinetics in its entire scope and the only one to include its implications for bioinformatics and systems biology. Multi-enzyme complexes and cooperativity are therefore treated in more detail than in any other textbook on the market